Methodology for assessing embryonic cracks development in structures under high‐cycle multiaxial random vibrations. Issue 1 (15th June 2017) - Vantadori, S.; Haynes, R.; Fortese, G.; Habtour, E.; Ronchei, C.; Scorza, D.; Zanichelli, A.
Abstract: The myriad applicability of the frequency‐domain critical plane criterion is outlined in order to evaluate and track the progression of fatigue damage in metallic structures subjected to high‐cycle multiaxial random vibrations. The fatigue assessment using the given criterion is performed according to the following stages: (i) critical plane definition, (ii) power spectral density evaluation of an equivalent normal stress and (iii) computation of the damage precursor and fatigue life. The frequency‐domain critical plane criterion is validated using experimental results related to (a) AISI 1095 steel cantilever beams under nonlinear base vibration, (b) 18G2A steel and (c) 10HNAP steel round specimens under random non‐proportional combined flexural and torsional loads.